Awareness Level on Sustainable Development Practices Among Postgraduate Students in Upsi, Perak - Ibrahim, Mohd Hairy; Hashim, Mohd Hashiq; a/l Mariyappan, Raman; Ismail, Mazlan; Singh, Balbir Singh Mahinder; Sathivelu4, Muttamah; Krishnan (International Journal of Psychosocial Rehabilitation, 2020)
Sustainable practices in campus development plan are crucial especially in preserving the environment in all universities. This study aims to identify the level of awareness of postgraduate students in Universiti Pendidikan Sultan Idris (UPSI). The data is collected using qualitative method by using questionnaire which distributed to 351 random postgraduate students in UPSI. The level of awareness is measured from the aspect of knowledge, perception, comfort, realization, and appreciation in campus sustainable development practices. The results showed that perception and comfort aspects showed high level (M = 4.03, SP = 0.59) and (M = 4.13, SP = 0.53) respectively, while knowledge, realization, and appreciation aspects showed moderate level (M = 3.45, SP = 0.81), (M = 3.65, SP = 0.66), and (M = 3.41, SP = 0.89) respectively. This finding explains postgraduate students have moderate level of knowledge about sustainable development practices that are crucial in understanding sustainability. All universities should empower and implement sustainable development practices in campus to increase all of the student knowledge especially in sustainability.